A study of relationship between employee engagement and employee performance at Ministry of Higher Education (MOHE) / Nurul Farrah Illyanie Roslan - Roslan, Nurul Farrah Illyanie (Faculty of Business and Management, 2017)
The purpose of this study is to investigate the relationship between employee engagement and employee performance. A sample of 169 respondents was selected through convenience sampling. Questionnaire was used as the instrument to collect responses. Data has been collected at Ministry of Higher Education (MOHE). From the analysis conducted, result has proven that there was a significant relationship between independent variable which are leadership, work environment, and teamwork and co-worker and dependent variable which is employee performance. Teamwork and co-worker were identified as the most significance variables influencing employee performance through the multiple regression analysis conducted.